Changes in the Hearing Thresholds of Infants Who Failed the Newborn Hearing Screening Test and in Infants Treated in the Neonatal Intensive Care Unit - Min-Young Kang; Sung-Wook Jeong; Lee-Suk Kim (Clinical and Experimental Otorhinolaryngology, 2012)
ObjectivesThe aim of this study was to investigate changes in the hearing thresholds during the first year of life in infants who failed the newborn hearing screening (NHS) test and of infants treated in the neonatal intensive care unit (NICU).MethodsFrom March 2007 to November 2010, 193 healthy infants who failed the NHS test and 51 infants who were treated in the NICU were referred for evaluation of hearing acuity. Their hearing was evaluated using impedance audiometry, auditory brainstem response (ABR), and otoacoustic emission before 6 months of age, and follow-up hearing tests were administered before 12 months of age. Changes in their hearing thresholds were then analyzed.ResultsOf the 193 healthy infants who failed the NHS test, 60 infants (31%) had normal hearing acuity, 126 infants (65%) had sensorineural hearing loss (SNHL, ABR threshold ≥40 dB) and 7 infants (4%) had auditory neuropathy (AN). On the follow-up hearing tests, which were conducted in 65 infants, 6 infants showed a hearing threshold deterioration of more than 20 dB, and 19 infants showed a hearing threshold improvement of more than 20 dB. Of the 51 infants who were treated in the NICU, 38 infants (75%) had normal hearing acuity, 12 infants (24%) had SNHL, and one infant (2%) had AN. In the follow-up hearing tests, which were performed in 13 infants, one infant with normal hearing progressed to severe hearing loss. Five infants who had SNHL showed a hearing threshold improvement of more than 20 dB, and 4 infants recovered to normal hearing.ConclusionThe hearing thresholds of infants with congenital SNHL can change during the first year of life; therefore, the importance of administration of follow-up hearing tests is emphasized. Irreversible intervention such as cochlear implantation should be considered with great caution within the first year after birth.